The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1080/13803395.2023.2245110
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective neurocognitive functioning in functional motor symptoms and functional seizures: preliminary findings

Susannah Pick,
L.S. Merritt Millman,
Yiqing Sun
et al.

Abstract: Introduction This study aimed to provide a preliminary assessment of objective and subjective neurocognitive functioning in individuals with functional motor symptoms (FMS) and/or functional seizures (FS). We tested the hypotheses that the FMS/FS group would display poorer objective attentional and executive functioning, altered social cognition, and reduced metacognitive accuracy. Method Individuals with FMS/FS (n = 16) and healthy controls (HCs, n = 17) completed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Feedback was elicited from participants, which has now been incorporated into this protocol. The findings of the pilot study have been reported elsewhere [ 10 , 23 25 ].…”
Section: Methodsmentioning
confidence: 67%
“…Feedback was elicited from participants, which has now been incorporated into this protocol. The findings of the pilot study have been reported elsewhere [ 10 , 23 25 ].…”
Section: Methodsmentioning
confidence: 67%
“…The recruitment/screening processes and eligibility criteria for the study are detailed in online supplemental table 1 and previous publications. 16 38 The FND sample were recruited through FND charities (FND Hope UK, FND Action) and social media (eg, Twitter). HCs were recruited from the local area.…”
Section: Participantsmentioning
confidence: 99%